Behavior problems of children in foster care: Associations with foster mothers' representations, commitment, and the quality of mother–child interaction. (October 2015) - Dubois-Comtois, Karine; Bernier, Annie; Tarabulsy, George M.; Cyr, Chantal; St-Laurent, Diane; Lanctôt, Anne-Sophie; St-Onge, Janie; Moss, Ellen; Béliveau, Marie-Julie
Abstract: This study investigated different environmental and contextual factors associated with maltreated children's adjustment in foster care. Participants included 83 children (52 boys), ages 1–7 years, and their foster caregivers. Quality of interaction with the foster caregiver was assessed from direct observation of a free-play situation; foster caregiver attachment state of mind and commitment toward the child were assessed using two interviews; disruptive behavior symptoms were reported by foster caregivers. Results showed that quality of interaction between foster caregivers and children were associated with behavior problems, such that higher-quality interactions were related to fewer externalizing and internalizing problems. Foster caregivers' state of mind and commitment were interrelated but not directly associated with behavior problems of foster children. Type of placement moderated the association between foster caregiver commitment and foster child behavior problems. Whereas greater foster caregiver commitment was associated with higher levels of adjustment for children in foster families (kin and non-kin), this was not the case in foster-to-adopt families. Finally, the associations between foster child behavior problems and history of maltreatment and placement related-risk conditions fell below significance after considering child age and quality of interaction with the foster caregiver. Findings underscore the crucial contribution of the foster caregiver–child relationship to fostering child adjustment and, thereby, have important implications for clinical services offered to this population.